2022
DOI: 10.1002/jmv.28369
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of secondary attack rate and viable virus shedding between patients with SARS‐CoV‐2 Delta and Omicron variants: A prospective cohort study

Abstract: There are limited data comparing the transmission rates and kinetics of viable virus shedding of the Omicron variant to those of the Delta variant. We compared these rates in hospitalized patients infected with Delta and Omicron variants. We prospectively enrolled adult patients with COVID‐19 admitted to a tertiary care hospital in South Korea between September 2021 and May 2022. Secondary attack rates were calculated by epidemiologic investigation, and daily saliva samples were collected to evaluate viral she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In contrast, early viral variants required a longer time to be cleared from the upper respiratory tract. [26][27][28] In this study, the median duration of negative conversion duration was 7 days for both asymptomatic and mild symptomatic patients, which might indicate that asymptomatic and mild symptomatic patients carry the virus and are infectious for a similar duration of time. It was also worth noting that the symptomatic patients had significantly lower C t values than the asymptomatic patients in the study.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In contrast, early viral variants required a longer time to be cleared from the upper respiratory tract. [26][27][28] In this study, the median duration of negative conversion duration was 7 days for both asymptomatic and mild symptomatic patients, which might indicate that asymptomatic and mild symptomatic patients carry the virus and are infectious for a similar duration of time. It was also worth noting that the symptomatic patients had significantly lower C t values than the asymptomatic patients in the study.…”
Section: Discussionmentioning
confidence: 58%
“…Our results found that 225 (40.8%) patients achieved a virus‐free status within 7 days (data not shown). In contrast, early viral variants required a longer time to be cleared from the upper respiratory tract 26–28 . In this study, the median duration of negative conversion duration was 7 days for both asymptomatic and mild symptomatic patients, which might indicate that asymptomatic and mild symptomatic patients carry the virus and are infectious for a similar duration of time.…”
Section: Discussionmentioning
confidence: 60%
“…First, the study period in the Ct group coincided with a predominance of the Omicron SARS-CoV-2 variant. Omicron exhibited a shorter duration of PCR positivity and viable virus shedding than Delta [ 22 ]. In addition, a higher proportion of patients were immunized against SARS-CoV-2 infection in the Ct group.…”
Section: Discussionmentioning
confidence: 99%
“…Although COVID‐19 vaccines were developed rapidly and the vaccination was actively advocated for, constant viral mutations affected the efficacy of approved vaccines 2 . The infectivity and immune escape ability of SARS‐CoV‐2 variants constantly changed, which caused different disease characteristics in the epidemic dominated by the original strain to the Omicron variant, and the Omicron variant had higher infectivity and immune escape ability 3 . In view of the high infectivity and pathogenicity of SARS‐CoV‐2, China still adhered strictly to epidemic prevention and control and took the safety and health of people as the priority before the launch of the “New Ten Rules” policy.…”
Section: Introductionmentioning
confidence: 99%
“…2 The infectivity and immune escape ability of SARS-CoV-2 variants constantly changed, which caused different disease characteristics in the epidemic dominated by the original strain to the Omicron variant, and the Omicron variant had higher infectivity and immune escape ability. 3 In view of the high infectivity and pathogenicity of SARS-CoV-2, China still adhered strictly to epidemic prevention and control and took the safety and health of people as the priority before the launch of the "New Ten Rules" policy. The epidemic wave, in which the Omicron subvariant was dominant, in Shanghai and Guangzhou was successfully controlled and prevented through the "dynamic zeroing" strategy.…”
mentioning
confidence: 99%